2018
DOI: 10.1155/2018/3431942
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of L-Tryptophan on Growth and Optical Properties of PbS Nanocrystalline Thin Films

Abstract: The growth through the green chemical bath of PbS doped systematically with the biomolecule L-tryptophan led to growth of hybrid, inorganic-organic, nanocrystalline thin films onto glass slides at T~80°C. The thickness was found in the range of 230-140 nm. Morphological changes were analyzed using atomic force microscopy (AFM). FTIR (Fourier-transform infrared spectroscopy) spectra showed broad absorption bands located at~3450 cm −1 attributed to stretching of the H 2 O molecules and two small absorption bands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…This enables QDSCs to trap the photon energy in the entire UV-Vis spectral region. Wavelengths similar to those obtained in this study for OCT-PbS/HDA have been reported as produced by the recombination of excitons shallowly trapped in electron-hole pairs by [32,43]. Table 1 and Figure 9 illustrate the current-voltage (J−V) characteristics of the QDSSCs of OCT-PbS/HDA and OCT-PbS photosensitizers under illumination.…”
Section: Bode Plot Results Of Metal Sulfides Nanoparticlessupporting
confidence: 80%
See 2 more Smart Citations
“…This enables QDSCs to trap the photon energy in the entire UV-Vis spectral region. Wavelengths similar to those obtained in this study for OCT-PbS/HDA have been reported as produced by the recombination of excitons shallowly trapped in electron-hole pairs by [32,43]. Table 1 and Figure 9 illustrate the current-voltage (J−V) characteristics of the QDSSCs of OCT-PbS/HDA and OCT-PbS photosensitizers under illumination.…”
Section: Bode Plot Results Of Metal Sulfides Nanoparticlessupporting
confidence: 80%
“…The height clusters of both samples depicted an insignificant change around 0.328 and 1.35 µm, which connotes smaller nanocrystals [35]. The images displayed small spherical nanocrystals with uniform distribution and size in the crystalline phase in both samples, indicating compact nanoparticles [32] and in further agreement with the XRD results. In order to evaluate electrocatalytic abilities and the reaction kinetics of PbS/HDA and PbS 120 photosensitizers, the cyclic voltammetry (CV) measurements were adopted with three-electrode 121 systems [36].…”
Section: Atomic Force Microscopysupporting
confidence: 85%
See 1 more Smart Citation